A Multimodal Discourse Analysis of Political Speeches: The Case of Donald Trump’s 2016 Election Speeches - Mohamed Elsanhoury; Abeer M. Refky M. Seddek; Névine M. Sarwat; Riham. E. A. Debian (Universitas Sanata Dharma, 2020)
This paper investigates the different verbal and non-verbal meaning making resources manifested in the speeches of Akron, Ohio and Phoenix, Arizona delivered by Donald Trump during his presidential campaign in 2016. The way verbal and non-verbal resources combine or interact intersemiotically unravels how Donald Trump attempts to affect his audience and reveal his populist leadership. For that end, the researcher carried out an analysis that is divided into two sections. Section one is devoted to a ‘themes’ analysis to isolate the overarching themes and illuminate the major topics addressed by President Donald Trump to seek his audience’s support. Section two follows SF-MDA which relies on Halliday’s systemic functional linguistics (Halliday, 1978, 1994; Halliday Matthiessen, 2004/2014) for the analysis of verbal meaning- making resources and Kress and Van Leeuwen’s visual grammar (1996/2006) for the analysis of non-verbal resources. The analysis reveals that both verbal and non-verbal meaning-making resources, in terms of representational, interactive and compositional meanings, work intersemiotically to deliver a full account of meaning and unravel Donald Trump's populist leadership.